149k views
5 votes
Guys, please help me with this problem. Thank you

Guys, please help me with this problem. Thank you-example-1
User CptanPanic
by
5.2k points

1 Answer

3 votes

Ok so the formula for point-slope is:


y - y 1 = m(x - x1)

m=slope

y1 = y point that's given

x1 = x point that's given

The problem says "use the point (-1,-4)"

so we will put it into our equation.

(-1,-4)

-1 is our x, and -4 is our y, now we can put it into the equation.


y - ( - 4) = m(x - (- 1))

Now we need to find the slope using:


(y2 - y1)/(x2 - x1)

y2=4

x2=3

y1=-4

x1=-1


(4 - ( - 4))/(3 - ( - 1)) = (8)/(4) \: or \: 2m=2

So the answer is..


y - ( - 4) = 2(x - ( - 1))

User Haydar
by
5.2k points